Hubungan Indikator Obesitas Terhadap Kadar Total Kolesterol Dan Trigliserida Pasien Penyakit Jantung - Yuliana Salman; Norhasanah Norhasanah (HB PRESS, 2018)
The main cause of heart disease (cardiovascular) is manifestation of arterosclerosis in coronary arteries. Risk factors for coronary heart disease are abnormalities of lipid profile and obesity. Waist circumference is an indicator used to determine the amount of excess fat in the abdomen. Based on the research, the higher ratio of waist circumferencewill be followed by high LDL cholesterol, triglyceride levels and total cholesterol levels. The purpose of this study is the association of obesity indicators with total cholesterol and triglyceride levels of heart disease patients in the Heart Polyclinic of RSUD Brig. H. Hasan Basry Kandangan. This research is an observational analytic research and use cross sectional design. The sample in this study amounted to 78 respondents (48 men and 30 women) with accidental sampling technique. Data analysis with Pearson correlation test with p value <0,05. Based on the research that has been done, the results obtained thatratio of waist circumference ideal of male respondents as much as 30 respondents and women as many as 9 respondents. Total cholesterol content of respondents mostly in the high category (â‰¥ 240 mg/dl), which is 41 respondents; triglyceride levels of respondents are mostly in the high category (250-500 mg/dl), as many as 38 respondents. There is a relationship between ratio of waist circumference with total cholesterol and triglyceride levels of respondents at H. Hasan Basry Kandangan Hospital.